FACTORS DRIVING ONLINE PURCHASE INTENTION OF THAI ELDERLY: APPLYING UTAUT2 AND TRUST FOR SUSTAINABLE DIGITAL COMMERCE - ทุนร่องช้าง เชาวรัตน์; คฤหโยธิน ธัญทิพย์; ปู่เกตุแก้ว กนต์ณัฐ; รัศมีวงษ์จันทร์ อุษณีย์ (Thai Interdisciplinary and Sustainability Review, 2026)
This study analyzed factors influencing online purchase intention among Thai elderly in E-marketplaces, applying the UTAUT2 model and trust. Data were collected from 520 elderly online shoppers using validated questionnaires and analyzed using confirmatory factor analysis. Results showed that the measurement model met the required fit indices, indicating a strong fit with the empirical data. Nine latent variables—effort and performance expectancy, social influence, facilitating conditions, price value, hedonic motivation, habit, trust, and online purchase intention—were confirmed with appropriate factor loadings. This substantiates the model’s robustness in predicting elderly online buying behavior. These findings are crucial for developing user-centric e-commerce platforms tailored to the specific needs of older adults, fostering their active participation in the digital economy, and ultimately contributing to a more inclusive and sustainable aging society in Thailand.